Desarrollo del talento humano como estrategia para mejorar el desempeño organizacional (2020)
Performance? It is a word which all the people in his diary of living have proceeded to use it, without knowing that he is applying said term, it is of those words where you are always using it for any procedure executed. It is with what virtues, abilities, merits, experiences the effort with which you execute any activity. He will then give to his knowledge what the performance of his collaborators and managers is for organizations. As the different authors see how bad planning really affects performance, such as the relationship between human talent strategies and the organization's performance. They will show how the paradigms are of great importance and in turn a factor that implies for the good and bad performance of the collaborators for the organization.